EDUARDO CABALLERO CALDERÓN Y EDICIONES GUADARRAMA: EDICIÓN Y VISIBILIDAD LITERARIA ENTRE COLOMBIA Y ESPAÑA, 1954-1960. - Murillo Sandoval, Juan David (Revista Chilena de Literatura, 2021)
This article studies the publishing activity of the Colombian writer Eduardo Caballero Calderón in Guadarrama Ediciones, the publishing house he founded in Madrid in 1954 together with the Spanish publisher Manuel Sanmiguel and co-directed until 1960. Based on a reconstruction of the Guadarrama catalog between 1954 and 1960, and through an analysis that links the history of the book with the sociology of literature, it is argued that Guadarrama was used by Caballero Calderón as a platform to gain recognition within the Spanish literary scene, as well as to orchestrate the international visibility of his literary work and that of other Colombian authors who were friends or close to his Hispanist thought.